Analysis of Accident-Prone Areas on The Kalimalang Canal Inspection Road, East Jakarta - Bayu Sugianto; Widodo Budi Dermawan (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
The number of traffic accidents that increase every year can be caused by factors such as drivers, vehicles, roads and the environment. In Indonesia, traffic accidents are one of the problems in the transportation sector. Prevention taken so far to anticipate accidents is only based on data on the quantity of accidents that have occurred. Whereas the factors or events that can cause accidents are the biggest contributor to accidents. For example, driving a vehicle in an orderly manner, driving at a speed above the average determined traffic regulation and non-standard road conditions. This research was conducted to identify accident-prone locations in an area by identifying and analyzing each segment based on point coordinates in the accident data and applying it to the AEK method. The research location is on the Kalimalang Canal Inspection road, East Jakarta which is divided into 5 segments. And these segments start from the border of Bekasi with East Jakarta to Cawang East Jakarta. The results show that the research location has the potential as an accident-prone area where the location is in segment 5 and on these roads after surveying it is found that there are several points. which do not have road markings, minimal road signs, several damaged road points, and incomplete street lighting. Which can result in traffic accidents